If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 13 = 3x + 65 Reorder the terms: 13 + 7x = 3x + 65 Reorder the terms: 13 + 7x = 65 + 3x Solving 13 + 7x = 65 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 13 + 7x + -3x = 65 + 3x + -3x Combine like terms: 7x + -3x = 4x 13 + 4x = 65 + 3x + -3x Combine like terms: 3x + -3x = 0 13 + 4x = 65 + 0 13 + 4x = 65 Add '-13' to each side of the equation. 13 + -13 + 4x = 65 + -13 Combine like terms: 13 + -13 = 0 0 + 4x = 65 + -13 4x = 65 + -13 Combine like terms: 65 + -13 = 52 4x = 52 Divide each side by '4'. x = 13 Simplifying x = 13
| 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= | | 1/3+2/3= | | 5y+11=6 | | -6.8(7.9+1.2x)+3.7=4.2x+40.90016 | | x^2-1x+40=0 | | (m+2n+1)(m-n+2)=5 | | x^2+12x+35x=0 | | 4x+13=-29-2 | | x+2x+6x+18x=160 | | 7(x*5)=9(6+4) | | 4m^2+4x=60 | | 3(2p-1)=8 | | -4x^2+24x-63=0 | | -2x^2-10x+14=0 | | 3(4x-7)=-33 | | 2xsquare+15y-13=0 | | -x^2-7= | | (-5)-(-11)=x |